Single femoral artery access is safe and feasible during transcatheter aortic valve replacement: a propensity score matched analysis - Yan, Yunfeng; Yao, Jing; Yuan, Fei; Liu, Xinmin; Luo, Taiyang; Lu, Zhinan; Chang, Sanshuai; Zhang, Qian; Liu, Ran; Yin, Chengqian; Song, Guangyuan (Frontiers in Cardiovascular Medicine, 2023)
Background: Transcatheter aortic valve replacement (TAVR) potentially may be significantly simplified by using the single artery access (SA) technique, which does not require a secondary artery access. Nevertheless, the safety and efficacy of this technique remains unclear. Our goal was to determine if single artery access TAVR (without upgrading the sheath size) is a feasible, minimally invasive procedure. Methods: Patients with symptomatic severe aortic stenosis who underwent TAVR via the femoral artery were consecutively enrolled in this study. Eligible individuals were divided into 2 groups: the SA group and the dual artery access (DA) group. The primary end point was device success (defined by the valve academic research consortium 3, VARC 3). A 6-month follow-up and propensity score matching analyses were performed. Results: After propensity score matching analysis, a total of 130 patients were included: 65 in the SA group and 65 in the DA group. The SA procedure achieved similar device success (95.4% vs. 87.7%; P=0.115) compared with the DA procedure. The SA procedure shortened the operating time (102 minutes vs. 125 minutes; P=0.001) but did not increase the X-ray time or dose. Both a 20 Fr and a 22 Fr sheath (without upgrading the sheath size) could be used for the SA procedure. There was no major vascular complication occurred in both groups. The incidence of minor main vascular and access complications in the SA group was comparable to those of the DA procedure (0.0% vs. 3.1%; P=0.156). Conclusions: The SA access procedure is a promising minimally invasive TAVR technique with a low incidence of vascular complications and a high incidence of device success. It is safe and possibly applicable in all TAVR procedures.